2016
DOI: 10.1016/j.watres.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of fluoroquinolone antibiotics: Mechanism, residual antibacterial activity and toxicity change

Abstract: In this paper, we studied the electrochemical oxidation mechanisms of three typical fluoroquinolone antibiotics (FQs), and investigated residual antibacterial activity and toxicity changes after oxidation processes. Electrochemistry coupled to mass spectrometry (EC-MS) was used to study the oxidation processes of ciprofloxacin (CIP), norfloxacin (NOR) and ofloxacin (OFL). Eight oxidation products for each parent compound were identified and their chemical structures were elucidated. The transformation trend of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…The proposed structures of the seven intermediates were basically deduced through direct photolysis and ·OH attack on benzene ring or piperazine ring. Similar intermediates were also seen in H 2 O 2 assisted photocatalysis [ 22 ], photoysis [ 21 ], gamma-ray irradiation [ 49 ], and electrochemical oxidation [ 50 ] of NOR.…”
Section: Resultsmentioning
confidence: 56%
“…The proposed structures of the seven intermediates were basically deduced through direct photolysis and ·OH attack on benzene ring or piperazine ring. Similar intermediates were also seen in H 2 O 2 assisted photocatalysis [ 22 ], photoysis [ 21 ], gamma-ray irradiation [ 49 ], and electrochemical oxidation [ 50 ] of NOR.…”
Section: Resultsmentioning
confidence: 56%
“…It has been reported that conventional biological processes (wastewater treatment plants) are incapable of removing antibiotic pollutants 24 . Many techniques have been used for the treatment of FQs-rich effluents such as electrochemical oxidation 25 , biodegradation 26 , photodegradation 27 , catalytic degradation 28 , micro-extraction 29 , oxidation (catalytic degradation) 30 , and adsorption 31 .…”
Section: Moxifloxacinmentioning
confidence: 99%
“…Ofloxacin (OFL) was used as the third generation of the fluoronone and has also been constantly detected in drinking water. Chlorine disinfection is the common method used to reduce OFL while the disinfection by-products, such as trihalomethanes (THMs) and haloacetic acids (HAAs), which have carcinogenic, teratogenic and abrupt effects, have been detected as well [5][6][7][8][9]. There are more than 700 kinds of Chlorination disinfection by-products which have been detected in drinking water and that are harmful to the human body, including more than 20 kinds of carcinogens and 50 kinds of mutants which threatens the drinking water safety and the health of the people [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%